ISOLATION OF TERPENOID AND DPPH SCAVENGER AND ANTIBACTERIAL TEST FROM N-HEXANE EXTRACT OF PATIKAN CINA (Euphorbia thymifolia L.) - Alamsyah Sudiarto, Akbar
Patikan cina (Euphorbia thymifolia L.) herbs were traditionally used for diarrhea, dysentry and hemorrhoid But, the information of their natural compounds was not known. Therefore, the aim of this research was to isolate triterpenoid and other natural compounds from E. thymifolia based on their antioxidant and antibacterial activity. Crude drug was extracted by n-hexane, ethyl acetate, dan ethanol 96% gradually using reflux method. Extracts and subfractions were monitored by TLC under UV light of 254 and 366 nm, DPPH 0.2 % in methanol and Libermann- Burchard reagents. Antibacterial activity was observed with bioautography method against Escherichia coli (ATCC 8939) and Bacillus subtilis (ATCC 6633). MIC values were obtained using broth microdilution method. N-hexane extract was fractionated by VLC, centrifugal preparative TLC and preparative TLC. The purity of isolated compound was evaluated by single development and two dimensional TLC. Characterization was done by H-NMR. Based on phytochemical screening, patikan cina herbs contained flavonoid, quinone, hydrolysable tannin, and steroid/triterpenoid. A triterpene compound was succesfully isolated from n-hexane extract, with hopane skeleton. Monitoring by DPPH on TLC with solvent system of n-hexane – ethyl acetate – methanol (8:2:1) showed n-hexane extract contained a component that scavanged free radical with Rf 0,6. In solvent system of n-hexane – ethyl acetate (9:1), two free radical scavangers were detected with Rf 0,3 and 0,4. N-hexane extract inhibited E.coli and B. subtilis with its MIC values were 128 ppm and 64 ppm, respectively. Based on bioautography, antibacterial component from n-hexane had Rf value 0,31 in solvent system n-hexane – ethyl acetate – methanol (4:1:1). A triterpene compound was isolated from patikan cina herbs with hopane structure. N-hexane extract of patikan cina at least had two free radical scavengers and this extract showed antibacterial activity against E. coli dan B. subtilis with MIC 128 ppm and 64 ppm, respectively.